Dynamics of physical fitness changes in preschool children, schoolgirls and female students of Eastern Siberia (Russia) - V.Y. Lebedinskiy; E.A. Koipysheva; L.D. Rybina; M.D. Kudryavtsev; L.K. Sidorov; N.N. Zukanov; S. A. Doroshenko; T. A. Kondratyuk; H. H. Alshuvaіli (Physical Education of Students, 2018)
Purpose : the analysis of physical fitness dynamics of the preschool children, schoolgirls and female students living in the region with an intense ecological situation. Material and methods . In total were surveyed: 1580 preschool children (age 4-7 years), 3211 schoolgirls (age 7-17 years) and 5827 female students (age 17-21 years). It was applied physical fitness tests of various groups of Russia population. Results : It was determined three essential periods of the main characteristics changes of physical fitness. The preschool age is characterized by the expressed gain of results. The lowest characteristics were revealed in senior age (after 17-18 years). Female students have relative stabilization value of these indicators. Conclusions : it is necessary to change the content of the educational process of physical training in educational institutions of the region.